Integrasi Teknologi Digital dalam Pembelajaran Pendidikan Agama Islam di Era Industri 4.0 - Ridwan Ridwan (Proceedings Series on Social Sciences & Humanities, 2022)
The purpose of this study is to describe theoretically appropriate digital technology and the determinants of the success of its application in the implementation of Islamic religious education learning at SMPIT. Khairul Imam Medan. This research uses a literature study approach. The selection of literary works is based on two considerations of criteria, namely (1) the literary work that is used as the basis has a direct relationship with the topic of the question to be revealed; and (2) the validity and credibility of the literature can be trusted, which is sourced from literature published by reputable publishers. From the results of this study, digital technology was obtained that was suitable for the implementation of Islamic religious education learning at SMPIT. Khairul Imam is a Google Workspace for Education with complete learning support facilities. In addition, the suitability of this technology is also caused by human resources and infrastructure at SMPIT. Khairul Imam is also sufficient. Finally, it can be concluded that with various learning technology facilities provided by Google Workspace for Education, the implementation of online Islamic religious education learning at SMPIT. Khairul Imam can be implemented and work well.